PENGARUH MODEL RELATING, EXPERIENCING, APPLYING, COOPERATING, AND TRANSFERRING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX SMPN 7 PADANG - Zilvia, Vicka; Mukhni, Mukhni (Jurnal Edukasi dan Penelitian Matematika, 2024)
The ability that students must achieve is the ability to solve mathematical problems. It can be seen from the results of the initial assessment that problem-solving skills in class IX SMP Negeri 7 Padang need to be improved. This study examines the development of mathematical problem-solving skills during the application of the REACT model and analyzes students' abilities using the REACT model superior to the direct learning model. Nonequivalent only posttest control grub research design with quasi-experimental method, and random sampling technique. From the results of the hypothesis test, P-value = 0.000. It can be concluded that the problem-solving ability of students applied by the REACT model is superior to the direct learning model.Keywords: Model REACT, Mathematical Problem Solving  Skills, Direct Learning